Lifestyle habits and diseases amongst rural geriatrics population - Prakash, Singh Jai; Bihari, Gupta Shyam; Kumar, Singh Atul (International Journal Of Community Medicine And Public Health, 2017)
Background: Modern science through improved sanitation, vaccination, and antibiotics, and medical attention has eliminated the threat of death from most infectious diseases. Death from lifestyle diseases like heart diseases and cancers are now the primary causes of death. Everybody naturally has to die of something, but lifestyle diseases take people before their time. Aim & Objective of the study was to find out association of risk factors (BMI and occupation) with lifestyle related diseases among the rural elderly. Methods:This cross-sectional study was conducted during January 2015 to April 2015 in a rural (Bhojipura block) areas of district Bareilly, Uttar Pradesh. 121 elderly persons of age 60 years and above were selected by systematic random sampling method and interviewed on a predesigned pretested questionnaire by house to house visits in the study area. Data was analysed by percentage and Chi squire tests. Results: Mixed dietary habit (27.8%), alcohol (9.3%) and smoking addictions (31.5%) were more common in men while tobacco chewing (16.4%) and sedentary habit (71.6%) was more common in women. Prevalence of hypertension, diabetes and chronic liver diseases were more common in both obese/obesity and working group in comparison to non-obese/obesity and non- working group. Here association of diabetes and chronic liver diseases with occupation & body mass index (BMI) was found statistically significant (‹0.05). Conclusions:Present study observed higher prevalence of hypertension, diabetes and chronic liver diseases among working group as compared to non- working group. Present study also shows higher BMI increases risk factors for lifestyle diseases.